Young women living in Iran: gendered drivers influencing social participation and wellbeing. Issue 4 (19th May 2021) - Salehi, Asiyeh; Whitehead, Dean; Sebar, Bernadette; upadhyay, Ravi; Coyne, Elisabeth; Harris, Neil
ABSTRACT: This paper investigates the social participation and wellbeing outcomes of young Iranian women, using a concurrent mixed method. Findings demonstrated relatively low levels of structural and functional social support as well as low level of social participation at the community level, particularly local and national group participation compared with casual/informal group participation. The individuals who socialized more with friends, relatives, colleagues, neighbours, as well as those with higher civic participation, were more likely to report higher wellbeing, as measured through satisfaction with life, quality of life and healthier lifestyle behaviours. The most common themes regarding barriers to social participation included: lack of time, money, cultural and societal barriers such as low socialization/leisure opportunities/infrastructure in the neighbourhood, lack of community/civic groups, lack of the culture of volunteering/volunteer jobs and low level of trust in society. This study suggests that women are further united and focus on their internal power through challenging gender bias and creating a culture of transformational change; which, in turn, lends itself to positive well-being outcomes. Furthermore, studies are required among Iranian men, how they can advocate for women's rights and reconstruction of the gendered systems for the interest of both genders.